653 DRAFFT Dodging? Fixation Methods for Distal Radial Fractures Since 2014 In A UK Trauma Unit. (4th May 2021) - Gilbert, J; Akehurst, H; Mutimer, J
Abstract: Introduction: The 2014 randomised, controlled Distal Radius Acute Fracture Fixation Trial (DRAFFT) compared K-wires to internal fixation for management of dorsally displaced distal radius fractures. The authors found no clinical difference between the two fixation methods, concluding 'The results of this trial will reverse the trend towards locking-plate fixation for this injury'. Our study aimed to measure local change in practice since 2014. Method: From the DRAFFT CONSORT diagram, we calculated just 10.7% of eligible cases required locking plate fixation. 300 patients, 50 per year from 2014-19 meeting DRAFFT eligibility criteria undergoing fixation, were randomly selected from an electronic trauma database. Radiographs were reviewed to see whether patients received internal fixation or K-wires. Results: Age and sex distributions of the study sample were not significantly different to the DRAFFT population (p < 0.05). Over 60% of recruited patients received internal fixation each year. No increasing trend in use of K-wires was detected (p = 0.27). No trend was observed in either fixation method adjusting for intra versus extra-articular fractures (p = 0.36). Conclusions: Local practice remains unchanged in fixation of dorsally displaced distal radius fractures since 2014. Internal fixation remains the most prevalent surgery, and there has been no detectable increase in use of K-wires.